2015
DOI: 10.1186/s12960-015-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Developing effective policy strategies to retain health workers in rural Bangladesh: a policy analysis

Abstract: IntroductionRetention of human resources for health (HRH), particularly physicians and nurses in rural and remote areas, is a major problem in Bangladesh. We reviewed relevant policies and provisions in relation to HRH aiming to develop appropriate rural retention strategies in Bangladesh.MethodsWe conducted a document review, thorough search and review of relevant literature published from 1971 through May 2013, key informant interviews with policy elites (health policy makers, managers, researchers, etc.), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 27 publications
0
52
0
1
Order By: Relevance
“…Thus, we found that the majority of the students (60%) came from a rural background, and in general their intention towards taking up jobs in rural areas was quite positive. Evidence from other countries also suggests that training students with rural backgrounds increases the likelihood of taking rural jobs after the graduation (Laven and Wilkinson, 2003;Woloschuk and Tarrant, 2004;Wilson et al, 2009;Walker et al, 2012;Rawal et al, 2015). In the case of medical doctors, a systematic review showed that doctors with a rural background are twice as likely to work as rural doctors compared with those with an urban background (Laven and Wilkinson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we found that the majority of the students (60%) came from a rural background, and in general their intention towards taking up jobs in rural areas was quite positive. Evidence from other countries also suggests that training students with rural backgrounds increases the likelihood of taking rural jobs after the graduation (Laven and Wilkinson, 2003;Woloschuk and Tarrant, 2004;Wilson et al, 2009;Walker et al, 2012;Rawal et al, 2015). In the case of medical doctors, a systematic review showed that doctors with a rural background are twice as likely to work as rural doctors compared with those with an urban background (Laven and Wilkinson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Considering most healthcare workers' motivation to work in rural areas lasts only a limited number of years, setting up a clear duration of the assignment in rural areas and introducing a rotation system could be one policy option to improve the transparency. Many countries already implement a rotation system, but effectiveness seems to vary [22][23][24] . Thus, a rotation system with non-adherence to a transparent policy would further demotivate healthcare workers in rural areas 19 …”
mentioning
confidence: 99%
“…Low motivation has been identified by some studies as the second most important health workforce problem after staff shortages [63]. Corruption in the recruitment and promotion of health workers may affect their motivation and retention [64,65]. However, while there are several studies on health worker motivation, few explicitly mention corruption in HRH as a factor.…”
Section: Impact On Motivation Of Health Workersmentioning
confidence: 99%